Shaping the Motherhood of Indigenous Mexico - Smith-Oka, Vania, 1975- (Book collections on Project MUSE., 2013)
Ethnographically explores the construction of motherhood in indigenous Mexico. Adds to anthropological literature on reproduction, economic development, and motherhood. Explores how indigenous mothers are viewed and managed by welfare programs as well as how humor becomes a way for the women to cope with their own marginality. -- Provided by publisher.